Restless Subjects in Rigid Systems : Risk and Speculation in Millennial Fictions of the North American Pacific Rim. - Wegener, Susanne (American Culture Studies ;, 2014)
The anticipatory logic of speculation and preemptive politics of risk are increasingly gaining significance in a globalizing neoliberal world. This study traces risk and speculation as aesthetic and political-economic strategies in factual and fictional discourses emerging at the North American Pacific Rim within a decade around 2000. Its exemplary close readings in particular focus on three fictional texts (Kathryn Bigelow's Hollywood film »Strange Days±, 1995, Karen T. Yamashita's novel »Tropic of Orange±, 1997, and Larissa Lai's novel »Salt Fish Girl±, 2002) whose intricate aesthetics pass.